2021
DOI: 10.1002/jmri.27873
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Cardiac Magnetic Resonance Strain in Suspected Myocarditis With Preserved LV‐EF: A Comparison Between Patients With Negative and Positive Late Gadolinium Enhancement Findings

Abstract: Background: Late gadolinium enhancement (LGE) is absent in many patients with suspected myocarditis and preserved left ventricular ejection fraction (LV-EF), which poses difficulties in diagnosis and risk stratification. Purpose: To investigate the diagnostic and prognostic value of ventricular myocardial strain in patients with suspected myocarditis, preserved LV-EF, and negative Lake Louis Criteria (LLC) by comparing the findings in LGE negative and LGE positive patients. Study Type: Retrospective. Populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…The current study found that segmental PLS, PCS, and PRS values were markedly impaired in the edema and LGE positive segments, thus indicating that myocardial injury is more severe in the presence of LGE. These ndings are consistent with that by previous investigations (30,32). Strikingly, even reduced PCS values in edema-only and noninvolved segments can be detected as compared with healthy control segments.…”
Section: Severity Of Myocardial Injury and Segmental Myocardial Strai...supporting
confidence: 93%
See 1 more Smart Citation
“…The current study found that segmental PLS, PCS, and PRS values were markedly impaired in the edema and LGE positive segments, thus indicating that myocardial injury is more severe in the presence of LGE. These ndings are consistent with that by previous investigations (30,32). Strikingly, even reduced PCS values in edema-only and noninvolved segments can be detected as compared with healthy control segments.…”
Section: Severity Of Myocardial Injury and Segmental Myocardial Strai...supporting
confidence: 93%
“…Compared to global analysis, segmental myocardial strain analysis makes it possible to distinguish the myocardial injury in more detail. Recently, Chen et al (30) has found that even the values of GRS, GCS and GLS were signi cantly lower in the LGE negative (with or without edema) group than that in the control group. Impairment of the myocardial strain was more severe in patients with LGE positive myocarditis.…”
Section: Severity Of Myocardial Injury and Segmental Myocardial Strai...mentioning
confidence: 95%
“…Strain analysis by CMR also has been shown to have prognostic utility in myocarditis even in the setting of normal LV function[ 10 ]. Strain testing can be performed without use of contrast material and can be particularly useful in situations where contrast administration is challenging or contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial strain, acquired using the CMR feature tracking (FT) technique, quantifies atrial and ventricular systolic function in different dimensions, with left atrial (LA) and biventricular strains proving to have diagnostic and prognostic significance [ 8 , 9 ]. The prognostic value of ventricular strain has been demonstrated in other cardiac diseases [ 10 , 11 , 12 ] and myocarditis [ 13 , 14 , 15 ]. Luetkens et al [ 16 ] explored the alterations in left and right ventricular strain in the course of acute myocarditis and suggested that initial left ventricular (LV) longitudinal strain may serve as a new parameter for the prediction of functional recovery upon follow-up; however, they did not evaluate LA strain in their study.…”
Section: Introductionmentioning
confidence: 99%